MICROBIOLOGICAL INVESTIGATION ON VETIVERIA LAWSONII - VIJI SARAL ELEZABETH D,; RAMACHANDRAN P, (International Journal of Pharma and Bio Sciences, 2015)
Indian medicinal plants are playing an important role in the traditional healing system. Vetiveria lawsonii is the most important plant belongs to Poaceae family with great medicinal value. This study was aimed to investigate the microbiological activity of Vetiveria lawsonii. The various extracts of Vetiveria lawsonii were prepared by soxhlet extraction method using acetone, benzene, chloroform, ethanol, methanol and n-Hexane. The results were confirmed methanol extracts of Vetiveria lawsonii showing significant activity against selected microbes than other extracts. We recommend further research on this plant for possible pharmacological investigation of the various chemical active substances.